Volatile organic compound catalytic oxidation catalyst as well as preparation method and application thereof
By preparing a mesoporous catalyst of non-precious metal oxide, the problems of low metal utilization and low catalyst activity in the prior art are solved, and efficient VOC removal is achieved, which is relatively cheap and the preparation method is simple.
Patent Information
- Application Number
- CN202310786394.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, the metal utilization rate of non-precious metal VOC catalytic oxidation catalysts is low and the catalyst activity is not high, making it difficult to meet the needs of industrial VOC governance.
The catalyst precursor is prepared by adding ordered mesoporous materials to the impregnation liquid, drying and calcining, and removing the mesoporous materials with alkali etching to obtain a high specific surface area and rich pores. catalyst.
The metal utilization rate is improved, the catalytic performance is improved, and the VOC removal rate is achieved to reach 80% or higher, the price is relatively low and the preparation method is simple.
Smart Images

Figure BDA0004312490420000091 
Figure HDA0004312490440000011
Abstract
Description
Technical Field
[0001] The present invention relates to a volatile organic compound (VOCs) catalytic oxidation catalyst, in particular to a porous VOC catalytic oxidation catalyst formed of a non-noble metal oxide, and a preparation method and application thereof. Background Art
[0002] VOCs emitted from industrial processes are a major source of air pollution. They have a significant impact on the natural environment and human health. Catalytic oxidation is one of the most widely used and researched VOC control methods. In the presence of a catalyst, VOCs undergo flameless combustion at a relatively low ignition temperature, converting them into carbon dioxide and water while releasing heat. Catalytic oxidation is a typical gas-solid phase catalytic reaction. The catalyst lowers the activation energy of the reaction while simultaneously concentrating reactant molecules on the catalyst surface, thereby increasing the reaction rate. Catalytic oxidation treatment of VOCs boasts low ignition temperatures, low energy consumption, a wide range of applications, high removal rates, and pollution-free products. The core and key to catalytic combustion methods lies in catalyst design. Catalysts can be categorized into precious metal and non-precious metal catalysts based on their active components. Precious metal catalysts such as Pt and Pd have been successfully industrialized for many years and boast low ignition and complete combustion temperatures, as well as a wide range of applications. However, precious metal catalysts have drawbacks such as high cost and susceptibility to poisoning. Non-precious metals such as Cu, Co, Fe, Mn, and Ce have attracted considerable attention in recent years due to their relatively low price, variable valence states, and excellent resistance to poisoning. Catalyst structure is also a key factor influencing catalytic performance. During catalytic oxidation, VOC molecules adhere to the catalyst surface, undergo conversion, and then separate into products. Therefore, catalysts with a higher specific surface area and more pores facilitate the retention and conversion of VOC molecules on the catalyst surface or in its pores, and facilitate the discharge of products (such as CO₂ and H₂O).
[0003] Chinese patent CN11 3477252A discloses a method for preparing and applying a composite porous catalyst containing titanium and other transition metals. The method utilizes a hydrothermal synthesis method to synthesize a metal composite material, TiSiMOx, with high specific surface area and large mesopore volume, where M is Fe, Co, Ni, Cu, or Zn. This metal composite material contains both zeolite phases and other oxide phases, and exhibits excellent catalytic oxidation properties.
[0004] Chinese patent CN106753547A discloses a method for removing dibenzothiophene from oil using a Co / KIT-6 cubic mesoporous catalyst. The method comprises the following steps: weighing a certain amount of P123, stirring concentrated hydrochloric acid and deionized water at 35°C, adding n-butanol, maintaining stirring at 35°C for 1 hour, adding tetraethyl orthosilicate (TEOS) (wherein the molar ratio of P123:H2O:HCl:n-butanol:TEOS = 0.017:196.49:5.31:1.31:1), stirring for 24 hours, and hydrothermal treatment at 35°C for 24 hours. The resulting white crystals are filtered, washed, and calcined at 550°C to obtain KIT-6. The Co / KIT-6 catalyst is then prepared using an impregnation method. The synthesized Co / KIT-6 catalyst and the oxidant cyclohexanone peroxide were added to an n-octane solution containing a certain amount of dibenzothiophene (DBT) and quinoline. After the reaction, the solution was extracted twice with N,N-dimethylformamide (DMF). This method exhibits significant catalytic activity for both DBT and quinoline in the n-octane system. Furthermore, the catalyst preparation process is simple and highly reusable.
[0005] Chinese patent CN104998627A discloses a method for preparing a mesoporous-macroporous catalyst for the catalytic oxidation of formaldehyde, comprising the following steps: 1) preparing a polystyrene template; 2) preparing a mesoporous oxide sol; 3) placing the polystyrene template prepared in step 1) into a sealed container, and pumping the mesoporous oxide sol prepared in step 2) onto the pore walls of the polystyrene template under a vacuum of 0.098 MPa, followed by drying. This filling and drying process is repeated several times to obtain a mesoporous-macroporous monolithic TiO2, SiO2, or Al2O3 support; and then using an excess volume impregnation method to fill a precursor solution of the active component Pt onto the mesoporous-macroporous monolithic TiO2, SiO2, or Al2O3 support. The resulting catalyst is abbreviated as Pt / TiO2, Pt / SiO2, or Pt / Al2O3. This mesoporous-macroporous catalyst can be used for the catalytic oxidation of formaldehyde. The catalyst can be used to remove formaldehyde in indoor and other polluted environments, overcoming the problems of powdered solid catalysts being difficult to shape, having a large pressure drop during use, and having a low utilization rate of metal atoms.
[0006] Although various VOC catalytic oxidation catalysts have been prepared in the prior art, there has always been a demand in the art to develop various catalysts for the catalytic oxidation of VOCs. Summary of the Invention
[0007] The present invention addresses the issues of low metal utilization and catalytic activity in the non-precious metal catalytic oxidation of VOCs. To this end, the present invention provides a VOC catalytic oxidation catalyst composed of a non-precious metal oxide and having multiple mesoporous channels. The catalyst has a high specific surface area and abundant mesoporous channels, which can improve metal utilization and thus provide excellent performance in the catalytic oxidation of VOCs. The present invention also relates to a preparation method and application of the VOC catalytic oxidation catalyst.
[0008] In one aspect, the present invention provides a VOC catalytic oxidation catalyst, which is formed from a non-precious metal oxide and has a plurality of mesoporous channels, wherein the non-precious metal salt is selected from one or more of Cu, Co, Mn, Ce, and Zr.
[0009] In another aspect, the present invention provides a method for preparing a VOC catalytic oxidation catalyst, wherein the catalyst is formed of a non-noble metal oxide and has a plurality of mesoporous channels, and the method comprises the steps of:
[0010] providing an impregnation solution containing non-precious metals;
[0011] Adding ordered mesoporous material to the impregnation solution, drying, and calcining to obtain a catalyst precursor, which is a non-metallic oxide supported on the ordered mesoporous material;
[0012] The catalyst precursor is etched with a base to remove the ordered mesoporous material to obtain the catalyst.
[0013] In yet another aspect, the present invention provides use of the above-mentioned VOC catalytic oxidation catalyst in catalytic oxidation treatment of volatile organic compounds.
[0014] Compared with the VOC catalytic oxidation catalysts in the prior art, the catalyst of the present invention has the following advantages:
[0015] 1. The catalyst is composed of non-precious metal oxides and is relatively cheap.
[0016] 2. The catalyst has multiple mesoporous channels and a high specific surface area, which increases the utilization rate of the metal in the catalyst and improves the catalytic performance.
[0017] 3. The preparation method is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 TEM images of catalysts AD prepared in Examples 1-4. DETAILED DESCRIPTION
[0019] Except in the examples, all numerical values herein are to be understood as being modified in all instances by the term "about", whether or not "about" actually precedes the value.
[0020] The present invention relates to a VOC catalytic oxidation catalyst, which is formed from a non-noble metal oxide and has a plurality of mesoporous channels. The non-noble metal salt can be one or more of Cu, Co, Mn, Ce, and Zr.
[0021] The VOC catalytic oxidation catalyst of the present invention has a porous structure and has multiple mesoporous channels. In this article, the term "mesopore" refers to pores with an average pore size of 2-50 nm. The presence of mesoporous channels helps VOC molecules and reaction product molecules enter and exit the catalyst, thereby helping to improve catalytic performance. The specific surface area of the VOC catalytic oxidation catalyst of the present invention is 100-500, preferably 150-300 m 2 / g.
[0022] The present invention also relates to a method for preparing a VOC catalytic oxidation catalyst, wherein the catalyst is formed of a non-noble metal oxide and has a plurality of mesoporous channels, and the method comprises the steps of:
[0023] providing an impregnation solution containing non-precious metals;
[0024] Adding ordered mesoporous material to the impregnation solution, drying, and calcining to obtain a catalyst precursor, which is a non-metallic oxide supported on the ordered mesoporous material;
[0025] The catalyst precursor is etched with a base to remove the ordered mesoporous material to obtain the catalyst.
[0026] The impregnation solution containing non-precious metals can be a non-precious metal salt solution. The non-precious metal salt solution can be one or more nitrates, sulfates, or hydrochlorides of non-precious metals selected from Cu, Co, Fe, Mn, Ce, Zr, La, Mg, Ti, Li, Na, K, Rb, Cs, Ca, Ba, Sr, Cr, Mo, W, Ni, Re, Zn, Cr, Ga, Al, and Sn, preferably one or more nitrates of non-precious metals selected from Cu, Co, Mn, Ce, and Zr. The concentration of the metal salt solution is 0.01-5 mol / L, preferably 0.05-3 mol / L, and more preferably 0.08-1 mol / L.
[0027] The ordered mesoporous material can be selected from one or more of SBA-1, SBA-2, SBA-3, SBA-15, SBA-16, MCM-41, MCM-22, MCM-48, KIT-6, and MCM-50, and is preferably selected from one or more of SBA-15, SBA-16, MCM-41, MCM-22, MCM-48, and KIT-6.
[0028] When the ordered mesoporous material is added to the impregnation solution, the amount of the ordered mesoporous material added is 0.1-30 wt %, preferably 1-20 wt %, and more preferably 5-15 wt % of the weight of the impregnation solution.
[0029] Impregnation can be carried out under conventional conditions in the art. Ultrasonic assisted impregnation is preferably used. The conditions for ultrasonic assisted impregnation may include: an ultrasonic frequency of 15-40 kHz, preferably 20-35 kHz; an ultrasonic power of 100-450 W / m 2 , preferably 200-400W / m 2 ; Temperature is 0-60℃, preferably 10-40℃; Time is 10-120min, preferably 20-60min.
[0030] The drying conditions may include: a temperature of 60-200° C., preferably 80-150° C.; and a time of 6-24 hours, preferably 10-18 hours.
[0031] The calcination conditions may include: a temperature of 300-700° C., preferably 400-600° C.; and a time of 2-12 hours, preferably 3-6 hours.
[0032] The alkali used for etching is selected from one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, and calcium hydroxide, preferably one of sodium hydroxide and potassium hydroxide. Preferably, an aqueous alkali solution is used for etching, and the concentration of the aqueous alkali solution is 0.1-10 mol / L, preferably 0.5-8 mol / L, and more preferably 1-6 mol / L. The etching can be carried out at a temperature of 50-200°C, preferably 80-150°C, for 2-12 hours, preferably 3-6 hours.
[0033] The method of the present invention may further include the steps of: after etching the catalyst precursor with an alkali to remove the ordered mesoporous material, performing solid-liquid separation, washing the solid, drying, and calcining. In one embodiment, the solid-liquid separation is performed by centrifugation. Washing can be performed by washing with deionized water until neutral. Drying and calcining can be performed as described above.
[0034] The catalyst of the present invention has a high specific surface area and abundant pores, which can improve metal utilization, resulting in excellent performance in the catalytic oxidation of VOCs. Therefore, the present invention also relates to the use of the VOC catalytic oxidation catalyst in the catalytic oxidation treatment of volatile organic compounds. In this application, a gas containing VOCs is introduced into a reactor containing the VOC catalytic oxidation catalyst at a space velocity of 4,000-25,000 h⁻¹, and the reaction is carried out at 150-450°C. The VOC catalytic oxidation catalyst of the present invention achieves a high VOC removal rate of 80% or higher, preferably 85% or higher, and more preferably 90% or higher.
[0035] Example
[0036] The present invention will be described in detail below by way of examples, which are intended to illustrate but not to limit the present invention in any way.
[0037] Example 1
[0038] 0.2 mol / L cerium nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 1:1 to form an impregnation solution. 2 g of SBA-15 was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 60 min at an ultrasonic frequency of 25 kHz and an ultrasonic power of 300 W / m 2 , the temperature was 35°C, and then stirred and evaporated to dryness at 80°C. The catalyst precursor was prepared by drying at 100°C for 12 hours and calcining at 500°C for 5 hours. The catalyst precursor was mixed with 100mL of 3mol / L NaOH solution at 90°C and stirred for 5 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 550°C for 4 hours to prepare Catalyst A.
[0039] Example 2
[0040] 0.1 mol / L manganese nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 2:1 to form an impregnation solution. 2 g of MCM-41 was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 60 min at an ultrasonic frequency of 30 kHz and an ultrasonic power of 250 W / m 2 , the temperature was 35°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 400°C for 5 hours to prepare a catalyst precursor. The catalyst precursor was mixed with 100mL of 2mol / L NaOH solution at 80°C and stirred for 4 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 500°C for 4 hours to prepare Catalyst B.
[0041] Example 3
[0042] 0.2 mol / L cerium nitrate solution and 0.1 mol / L copper nitrate solution were mixed in a volume ratio of 1:1 to form an impregnation solution. 2 g of SBA-16 was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 45 min at an ultrasonic frequency of 25 kHz and an ultrasonic power of 300 W / m 2, the temperature was 35°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 500°C for 5 hours to prepare a catalyst precursor. The catalyst precursor was mixed with 100mL of 4mol / L NaOH solution at 80°C and stirred for 5 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 500°C for 4 hours to prepare Catalyst C.
[0043] Example 4
[0044] 0.2 mol / L manganese nitrate solution and 0.1 mol / L copper nitrate solution were mixed in a volume ratio of 1:1 to form an impregnation solution. 2 g of KIT-6 was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 30 min at an ultrasonic frequency of 35 kHz and an ultrasonic power of 300 W / m 2 , the temperature was 35°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 500°C for 5 hours to prepare a catalyst precursor. The catalyst precursor was mixed with 100 mL of 4 mol / L NaOH solution at 90°C and stirred for 5 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 550°C for 5 hours to prepare Catalyst D.
[0045] Example 5
[0046] 0.3 mol / L cerium nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 1:1 to form an impregnation solution. 2 g of MCM-41 was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 60 min at an ultrasonic frequency of 25 kHz and an ultrasonic power of 300 W / m 2 , the temperature was 40°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 550°C for 5 hours to prepare a catalyst precursor. The catalyst precursor was mixed with 100mL of 2mol / L NaOH solution and stirred at 80°C for 5 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 500°C for 5 hours to prepare Catalyst E.
[0047] Example 6
[0048] 0.2 mol / L manganese nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 1:1 to form an impregnation solution. 2 g of MCM-48 was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 90 min at an ultrasonic frequency of 30 kHz and an ultrasonic power of 150 W / m2 , the temperature was 40°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 400°C for 5 hours to prepare a catalyst precursor. The catalyst precursor was mixed with 100 mL of 3 mol / L NaOH solution and stirred at 80°C for 4 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 450°C for 4 hours to prepare Catalyst F.
[0049] Example 7
[0050] 0.1 mol / L manganese nitrate solution and 0.1 mol / L cobalt nitrate solution were mixed in a volume ratio of 3:1 to form an impregnation solution. 2 g of MCM-22 was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 60 min at an ultrasonic frequency of 30 kHz and an ultrasonic power of 300 W / m 2 , the temperature was 25°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 400°C for 5 hours to obtain a catalyst precursor. The catalyst precursor was mixed with 100mL of 2mol / L NaOH solution at 80°C and stirred for 4 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 600°C for 4 hours to obtain Catalyst G.
[0051] Example 8
[0052] 0.1 mol / L manganese nitrate solution and 0.1 mol / L copper nitrate solution were mixed in a volume ratio of 2:1 to form an impregnation solution. 1 g MCM-41 and 1 g SBA-15 were added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 60 min at an ultrasonic frequency of 30 kHz and an ultrasonic power of 250 W / m 2 , the temperature was 40°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 400°C for 5 hours to obtain a catalyst precursor. The catalyst precursor was mixed with 100 mL of 4 mol / L NaOH solution at 80°C and stirred for 4 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 550°C for 4 hours to obtain Catalyst H.
[0053] Example 9
[0054] 0.2 mol / L copper nitrate solution and 0.2 mol / L zirconium nitrate solution were mixed in a volume ratio of 2:1 to form an impregnation solution. 2 g MCM-41 and 2 g SBA-15 were added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 30 min at an ultrasonic frequency of 25 kHz and an ultrasonic power of 400 W / m 2 , the temperature was 25°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 400°C for 5 hours to prepare a catalyst precursor. The catalyst precursor was mixed with 100 mL of 5 mol / L NaOH solution and stirred at 80°C for 4 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 500°C for 4 hours to prepare Catalyst I.
[0055] Example 10
[0056] 0.1 mol / L manganese nitrate solution and 0.3 mol / L zirconium nitrate solution were mixed in a volume ratio of 1:1 to form an impregnation solution. 3 g of SBA-15 was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 60 min at an ultrasonic frequency of 25 kHz and an ultrasonic power of 300 W / m 2 , the temperature was 40°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 400°C for 5 hours to prepare a catalyst precursor. The catalyst precursor was mixed with 100mL of 4mol / L NaOH solution at 80°C and stirred for 4 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 550°C for 4 hours to prepare Catalyst J.
[0057] Comparative Example 1
[0058] 0.1 mol / L manganese nitrate solution and 0.3 mol / L zirconium nitrate solution were mixed in a volume ratio of 1:1 to form an impregnation solution. 3 g of alumina was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 60 min at an ultrasonic frequency of 25 kHz and an ultrasonic power of 300 W / m 2 , the temperature was 40°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 400°C for 5 hours to obtain a catalyst precursor. The catalyst precursor was mixed with 100mL of 4mol / L NaOH solution at 80°C and stirred for 4 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 550°C for 4 hours to obtain catalyst K.
[0059] Comparative Example 2
[0060] 0.1 mol / L manganese nitrate solution and 0.1 mol / L copper nitrate solution were mixed in a volume ratio of 2:1 to form an impregnation solution. 2 g of titanium oxide was added to 20 mL of the impregnation solution, and deionized water was added to a total volume of 50 mL. Ultrasonic assisted impregnation was performed for 60 min at an ultrasonic frequency of 25 kHz and an ultrasonic power of 300 W / m 2 , the temperature was 40°C, and then stirred and evaporated to dryness at 80°C. After drying at 100°C for 12 hours, it was calcined at 400°C for 5 hours to obtain a catalyst precursor. The catalyst precursor was mixed with 100mL of 5mol / L NaOH solution at 80°C and stirred for 4 hours, and then centrifuged to obtain a solid. The solid was washed with deionized water until neutral, dried at 100°C, and then calcined in a muffle furnace at 500°C for 4 hours to obtain catalyst L.
[0061] The catalysts of Examples 1-10 and Comparative Examples 1-2 were respectively loaded into a fixed bed reactor to test their catalytic oxidation of VOCs. 3 VOCs simulated gas, which contains 200mg / m 3 Benzene, 600 mg / m 3 Xylene, 600 mg / m 3 p-Xylene, 600 mg / m 3 Methyl acetate. At a temperature of 300°C and a volume space velocity of 15000 h -1 The reaction was carried out under the conditions of . The concentration of VOC gas at the reactor outlet was detected by gas chromatography. The detection results are summarized in Table 1.
[0062] The specific surface areas of the catalysts of Examples 1-10 and Comparative Examples 1-2 were measured using a Micromeritics ASAP2020 adsorption instrument. The results are summarized in Table 1.
[0063] Transmission electron microscope (TEM) photos of catalysts AD of Examples 1-4. Specifically, catalysts AD were characterized using a JEOL-794 transmission electron microscope from JEOL, Japan. The test conditions were: the acceleration voltage of the transmission electron microscope was 200 kV. The catalyst sample was dispersed in anhydrous ethanol, fully ultrasonically vibrated, and then placed on a copper mesh surface for testing. The results are shown in Figure 2. Figure 1 shown.
[0064] Table 1 Test results of catalysts of Examples 1-10 and Comparative Examples 1-2
[0065]
Claims
1. A VOC catalytic oxidation catalyst, which is formed by a non-precious metal oxide and has a plurality of mesoporous channels, wherein the non-precious metal salt is selected from one or more of Cu, Co, Mn, Ce, and Zr.
2. The catalyst according to claim 1, having a specific surface area of 100-500 m 2 / g, preferably 150-300m 2 / g.
3. A method for preparing a VOC catalytic oxidation catalyst, wherein the catalyst is formed of a non-precious metal oxide and has a plurality of mesoporous channels, and the method comprises the steps of: Providing an impregnation solution containing a non-precious metal; Adding ordered mesoporous material to the impregnation solution, drying, and calcining to obtain a catalyst precursor, which is a non-metallic oxide supported on the ordered mesoporous material; The catalyst precursor is etched with a base to remove the ordered mesoporous material to obtain the catalyst.
4. The method of claim 3, wherein the impregnation solution containing non-precious metals is a non-precious metal salt solution, wherein the non-precious metal salt solution is one or more selected from the group consisting of nitrates, sulfates, and hydrochlorides of non-precious metals of Cu, Co, Fe, Mn, Ce, Zr, La, Mg, Ti, Li, Na, K, Rb, Cs, Ca, Ba, Sr, Cr, Mo, W, Ni, Re, Zn, Cr, Ga, Al, and Sn, preferably one or more selected from the group consisting of nitrates of non-precious metals of Cu, Co, Mn, Ce, and Zr. Preferably, the concentration of the non-precious metal salt solution is 0.01-5 mol / L, preferably 0.05-3 mol / L, and more preferably 0.08-1 mol / L.
5. The method of claim 3, wherein the ordered mesoporous material is selected from one or more of SBA-1, SBA-2, SBA-3, SBA-15, SBA-16, MCM-41, MCM-22, MCM-48, KIT-6, and MCM-50, preferably one or more of SBA-15, SBA-16, MCM-41, MCM-22, MCM-48, and KIT-6. Preferably, the amount of ordered mesoporous material added is 0.1-30 wt %, preferably 1-20 wt %, and more preferably 5-15 wt % based on the weight of the impregnation solution.
6. The method of claim 3, wherein the impregnation is performed by ultrasound-assisted impregnation, wherein the conditions for ultrasound-assisted impregnation include: The ultrasonic frequency is 15-40kHz, preferably 20-35kHz; the ultrasonic power is 100-450W / m 2 , preferably 200-400W / m 2 ; The temperature is 0-60°C, preferably 10-40°C; The time is 10-120min, preferably 20-60min.
7. The method of claim 3, wherein the drying conditions comprise: The temperature is 60-200°C, preferably 80-150°C; The time is 6-24 hours, preferably 10-18 hours, and The calcination conditions include: a temperature of 300-700° C., preferably 400-600° C.; and a time of 2-12 hours, preferably 3-6 hours.
8. The method of claim 3, wherein the alkali used for etching is selected from one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, and calcium hydroxide, preferably one of sodium hydroxide and potassium hydroxide. Preferably, etching is performed using an aqueous alkali solution, wherein the concentration of the aqueous alkali solution is 0.1-10 mol / L, preferably 0.5-8 mol / L, and more preferably 1-6 mol / L. Preferably, etching is performed at a temperature of 50-200° C., preferably 80-150° C., for 2-12 hours, preferably 3-6 hours.
9. Use of the VOC catalytic oxidation catalyst according to claim 1 or 2 in catalytic oxidation treatment of volatile organic compounds; Preferably, the catalytic oxidation treatment is carried out at a space velocity of 4000-25000h -1 , carried out at 150-450°C.
Citation Information
Cited By
In (at) CuO-SnO2-MnO-MgO (at) CePO4 core-shell structure catalyst and preparation method thereof
CN120286033A
Supported bifunctional catalyst for treating chlorine-containing organic matters in medical waste salt molten flue gas at low temperature as well as preparation method and application of supported bifunctional catalyst
CN122098670A